Rapid Stability Indicating RP-HPLC Method for Simultaneous Quantification of Related Impurities of Antiretroviral Drugs - Kalpana, J.; Himaja, M.; Anbarasu, C. (Asian Journal of Chemistry, 2015)
A simple, rapid and stability indicating reverse phase liquid chromatographic method has been developed for the simultaneous quantitative determination of emtricitabine, rilpivirine and tenofovir disoproxil fumarate and their related impurities in a combined dosage form. The pharmaceutical formulation along with individual active ingredients were subjected to stress conditions of hydrolysis (acid and base), oxidation and thermal degradation as per ICH guidelines. The chromatographic separation was achieved using an Xterra RP C18 (250 × 4.6 mm, 5 μm stationary phase with a linear gradient elution and the detection wavelength was set at 254 nm. The mobile phase consists of buffer and acetonitrile delivered at a flow rate of 1 mL/min. The stress samples were assayed against a reference standard and the mass balance was found to be close to 99 %. The proposed RP-HPLC method was validated with respect to linearity, precision, accuracy and robustness.